Science as Effective Social Communication - J. C. Kotze (Communicare)
Social scientists have by and large allenated the rest of society from science, and In this process have re moved themselves from the dally mundane matters and demands of social life, through the theoretical objectification of society. People con stituting society, on the other hand, are subjectively engaged in everyday social life. In its application of objec tive theory, science falls to share Emeaning in terms of subjective ex meaning with human beings who find perience. This article pursues the no tion that perception plays a crucial part in communication; that percep tion is shaped by experience; and that experience is historically and situationally specific. Objective the ory, being a deliberate attempt to transcend specific instances of sub. jective experiences both in time and place, is incompatible with the con tingency inherent in subjective ex perience. In trying to say too much by encompassing too much of mankind, objective theory has very little to say to people in real situations.